A comparative analysis of pace, work and gait during national championship cross-country and road running events - Macdermid, P. W.; Grayling, P. (The Journal of Sport and Exercise Science, 2021)
This study compared differences in running gait, intensity and performance across three national championship races comprised of different surface-conditions. Seven competitive under-20 male middle-distance athletes raced in all three events with no preparatory interference from researchers. The events comprised an asphalt road (Road) and dry, hard- pack (XC-dry) and wet, muddy (XC-wet) cross-country courses. Athletes wore GPS sports watches and inertial sensor (3 axis gyroscopes and accelerometers) foot pods to collect speed, total power output, form power output, propulsive power output, stride rate, ground- contact time, vertical oscillation, and leg spring stiffness data. The Road was quicker with greater total and propulsive power outputs (all p < 0.01), yet heart rate was not significantly different. There was no difference in form power or stride rate between Road, XC-dry and XC-wet. Road also demonstrated shorter ground-contact times and greater rate of force production during stance phase, greater leg spring stiffness (all p < 0.05) and greater (p < 0.01) and more variable stride length. Collectively, these findings indicate greater running economy during Road compared to XC-dry and XC-wet. Future research using spatiotemporal technology may consider how differences in running gait metrics over different surfaces and terrain profile influence training response(s).